The apothecary diaries. Volume 12 - Hyūga, Natsu (Square Enix Manga & Books, 2024)
Maomao joins a hunt...but is Jinshi the quarry?! Strong-armed into getting out more, Maomao attends a spooky soiree where court ladies share spine-tingling tales of terror as a diversion from their daily toil. While there are plenty of chills to go around, the thrills are perhaps few for the skeptical Maomao...until the evening takes an eerie turn! And she doesn't have long to wait for more excitement! Jinshi requests Maomao's presence on a hunting trip, and as ever, all is not as it seems when court intrigue and subterfuge are in play. When a break from a banquet on the hunt goes awry, master and servant soon find themselves in a very tight spot and and uncomfortably close quarters...